Information management goals and process failures during home visits for middle-aged and older adults receiving skilled home healthcare services after hospital discharge: a multisite, qualitative study. Issue 2 (17th July 2018) - Arbaje, Alicia I; Hughes, Ashley; Werner, Nicole; Carl, Kimberly; Hohl, Dawn; Jones, Kate; Bowles, Kathryn H; Chan, Kitty; Leff, Bruce; Gurses, Ayse P
Abstract : Background: Middle-aged and older adults requiring skilled home healthcare ('home health') services following hospital discharge are at high risk of experiencing suboptimal outcomes. Information management (IM) needed to organise and communicate care plans is critical to ensure safety. Little is known about IM during this transition. Objectives: (1) Describe the current IM process (activity goals, subactivities, information required, information sources/targets and modes of communication) from home health providers' perspectives and (2) Identify IM-related process failures. Methods: Multisite qualitative study. We performed semistructured interviews and direct observations with 33 home health administrative staff, 46 home health providers, 60 middle-aged and older adults, and 40 informal caregivers during the preadmission process and initial home visit. Data were analysed to generate themes and information flow diagrams. Results: We identified four IM goals during the preadmission process: prepare referral document and inform agency; verify insurance; contact adult and review case to schedule visit. We identified four IM goals during the initial home visit: assess appropriateness and obtain consent; manage expectations; ensure safety and develop contingency plans. We identified IM-related process failures associated with each goal: home health providers and adults with too much information (information overload); home health providers without complete information (information underload); home health coordinators needing information from many places (information scatter); adults' and informal caregivers' mismatched expectations regarding home health services (information conflict) and home health providers encountering inaccurate information (erroneous information). Conclusions: IM for hospital-to-home health transitions is complex, yet key for patient safety. Organisational infrastructure is needed to support IM. Future clinical workflows and health information technology should be designed to mitigate IM-related process failures to facilitate safer hospital-to-home health transitions.